Operational excellence, organizational culture, and agility: bridging the gap between quality and adaptability - Carvalho, André M. (2023)
Operational Excellence (OpEx) is understood by the quest to continuously improve performance. While used by organizations worldwide, the capacity of OpEx programmes to make organizations successful in unstable business environments has been challenged. This article aims to answer the research question of what the nature of the relationship between OpEx and Organizational Agility truly is. The authors have previously proposed a theoretical framework supporting the link between Operational Excellence, Organizational Culture, and Organizational Agility. While built on a strong conceptual background, this framework lacked empirical validation. Following the conclusion of ten industrial case studies, this article provides a summary of the key findings obtained in each case and integrates them into an updated conceptual model. As key findings, this study shows how Operational Excellence enablers and cultural orientation have an important role in the development and scaling up of Organizational Agility capabilities, highlighting how different contexts may influence these dynamics. This article offers a better understanding of the balance needed to maintain high operational performance levels while dealing with change. It connects and upholds the importance of Organizational Agility and of the cultural paradigm in the management of Quality in technical and technological organizations.